High-Impact Minimum Wages and Heterogeneous Regions - Philipp vom Berge; Hanna Frings; Alfredo R. Paloyo (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
We estimate the effects on wage and employment growth rates of the introduction and subsequent increases of a substantial minimum wage in the main construction industry of Germany. Using a regional dataset constructed from individual employment histories, we exploit the spatial dimension and border discontinuities of the regional data to account for spillovers between districts and unobserved heterogeneity at the local level. The results indicate that the minimum wage increased the wage growth rate for East Germany but did not have a significant impact on the West German equivalent. The estimated effect on the employment growth rate reveals a contraction in the East of about 2.6 to 3.1 percentage points for a one-standard-deviation increase in the minimum-wage bite, amounting to roughly half of the overall decline in the growth rate, but no significant change is observed for the West. – – In diesem Papier werden die Lohn- und Beschäftigungseffekte des Mindestlohns im deutschen Bauhauptgewerbe untersucht. Hierzu werden, basierend auf Individualdaten, Diskontinuitäten der Mindestlohnbetroffenheit auf Ebene der Kreise und kreisfreien Städte ausgenutzt. Gleichzeitig kontrollieren wir für unbeobachtbare regionale Unterschiede und mögliche Spillover-Effekte an den Grenzen der einzelnen Kreise. Die Ergebnisse zeigen, dass die Einführung des Mindestlohns in Ostdeutschland zu einer schnelleren Anhebung des Lohnniveaus geführt hat, während im Westen diesbezüglich kein Effekt zu erkennen ist. Bezogen auf das Beschäftigungswachstum kann festgehalten werden, dass bei einer Steigerung der Mindestlohnbetroffenheit um eine Standardabweichung die Wachstumsrate der Beschäftigung um ungefähr die Hälfte abnimmt. Dies entspricht ca. 2,6 bis 3,1 Prozentpunkten. Für Westdeutschland ist auch hier kein signifikanter Effekt beobachtbar.
Keywords: J31; J38; 330; construction sector; Germany; minimum wage; spatial heterogeneity; spatial panel data